2010
DOI: 10.3844/ajabssp.2010.363.369
|View full text |Cite
|
Sign up to set email alerts
|

Field Assessment of Anthracnose Disease Response for the Sorghum Germplasm Collection from the Mopti Region

Abstract: Problem statement: Sorghum anthracnose (Colletotrichum sublineolum) is a highly variable pathogen and new sources of host plant resistance are required for the development of resistant sorghum varieties. Germplasm collections are an important source of host plant resistance and screening germplasm will be essential to identify new sources of resistance. Approach: The sorghum (Sorghum bicolor) collection from the Mopti region of Mali was inoculated with Colletotrichum sublineolum and evaluated for foliar anthra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Colletotrichum gloeosporioides identified in this study has been reported as the most common and wide spread pathogen in all avocado growing region worldwide [ 36 38 ]. Further it has been associated with infection of other hosts such as almond, coffee, guava, apple, dragon fruit, cassava, mango, sorghum, and strawberry [ 2 , 15 , 39 ]. Though C. boninense identified is not very common in the study area, its sequence was identical to published sequence (KX 343044.1 and KU356916.1) in the Genbank.…”
Section: Discussionmentioning
confidence: 99%
“…Colletotrichum gloeosporioides identified in this study has been reported as the most common and wide spread pathogen in all avocado growing region worldwide [ 36 38 ]. Further it has been associated with infection of other hosts such as almond, coffee, guava, apple, dragon fruit, cassava, mango, sorghum, and strawberry [ 2 , 15 , 39 ]. Though C. boninense identified is not very common in the study area, its sequence was identical to published sequence (KX 343044.1 and KU356916.1) in the Genbank.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely grown in different countries of the world and is attacked by a number of diseases of which anthracnose is one of the most common especially in India and loss due to this disease is substantial (Slade et al, 1987). Anthracnose caused by C. gloeosporioides is reported on a wide variety of crop, including almond, avocado, apple, arabica coffee, guava, mango, dragon fruit, cassava, sorghum and strawberry (Amusa et al, 2005;Masyahit et al, 2009;Owolade et al, 2009;Erpelding, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The strategies for increasing production against fungal pathogens, genetic engineering, and classical breeding for the traits conferring tolerance and resistance could be a precise approach for decreasing the losses caused by them. All the areal parts of sorghum including tissues can be infested by anthracnose (Erpelding 2010). On all of the above ground tissues of the sorghum plant, anthracnose infection can be detected that includes seed, panicle, stalk, and leaf (Hess et al 2002;Thakur and Mathur 2000).…”
Section: Anthracnosementioning
confidence: 99%